Transition Planning: Keeping Cultural Competence in Mind. (May 2020) - Suk, Andrea L.; Sinclair, Tracy E.; Osmani, Kimberly J.; Williams-Diehm, Kendra
Transition planning must consider all aspects of the student's postsecondary goals. Although the makeup of personnel in educational settings are predominantly White, the number of students from culturally, ethnically, and linguistically diverse (CELD) backgrounds continues to grow. This article promotes personal reflection on cultural competence, suggests how to incorporate cultural responsiveness into transition planning, and recommends how special educators can develop strong, compliant transition goals for students from CELD backgrounds.